Glycation by glyoxal leads to profound changes in the behavior of dermal fibroblasts - Cécile Guillon; Sandra Ferraro; Sophie Clément; Marielle Bouschbacher; Dominique Sigaudo-Roussel; Christelle Bonod (BMJ Open Diabetes Research & Care)
Introduction Diabetes is a worldwide health problem that is associated with severe complications. Advanced Glycation End products (AGEs) such as Nε-(carboxymethyl)lysine, which result from chronic hyperglycemia, accumulate in the skin of patients with diabetes. The effect of AGEs on fibroblast functionality and their impact on wound healing are still poorly understood.Research design and methods To investigate this, we treated cultured human fibroblasts with 0.6 mM glyoxal to induce acute glycation. The behavior of fibroblasts was analyzed by time-lapse monolayer wounding healing assay, seahorse technology and atomic force microscopy. Production of extracellular matrix was studied by transmission electronic microscopy and western blot. Lipid metabolism was investigated by staining of lipid droplets (LDs) with BODIPY 493/503.Results We found that the proliferative and migratory capacities of the cells were greatly reduced by glycation, which could be explained by an increase in fibroblast tensile strength. Measurement of the cellular energy balance did not indicate that there was a change in the rate of oxygen consumption of the fibroblasts. Assessment of collagen I revealed that glyoxal did not influence type I collagen secretion although it did disrupt collagen I maturation and it prevented its deposition in the extracellular matrix. We noted a pronounced increase in the number of LDs after glyoxal treatment. AMPK phosphorylation was reduced by glyoxal treatment but it was not responsible for the accumulation of LDs.Conclusion Glyoxal promotes a change in fibroblast behavior in favor of lipogenic activity that could be involved in delaying wound healing.